3D conjugate natural convection in a vertical cylinder on the assumption of heat transfer to the environment - Sheremet, Mikhail Alexandrovich (Computational Continuum Mechanics, 2010)
Mathematical simulation of three-dimensional unsteady conjugate natural convection in a closed vertical cylinder having a local heat source in conditions of convective heat transfer to the environment in terms of dimensionless variables such as vector potential, vorticity vector, temperature has been carried out. Temperature and velocity fields and the average Nusselt number at the heat source surface as functions of key parameters, reflecting formation of different modes of mass transfer, momentum transport and energy transfer, have been obtained.
Keywords: conjugate heat transfer; natural convection; 3D modes; vertical cylinder; vector potential functions